PENGARUH KOMPETENSI, INDEPENDENSI DAN PENGALAMAN TERHADAP KUALITAS AUDIT APARAT INSPEKTORAT KOTA TOMOHON DALAM PENGAWASAN PENGELOLAAN KEUANGAN DAERAH - Bolang, Marietta Sylvie; Sondakh, Jullie J.; Morasa, Jenny (ACCOUNTABILITY, 2013)
This study examined the influence of the auditors’ competency, independency, and experiences towards audit quality of financial auditing of the staff of inspectorate in Tomohon City as part of their supervision function. The finding of this study could be an important input for improving the quality of financial management of the local government since the policy of decentralization has given the local governments authority not only to manage natural resources but also their financial sector. However, as could be seen there are still a lot of problems related to financial management mostly caused by the poor knowledge and skills related to financial auditing of government offici als responsible for this specific task. It is common to find inconsistency in the financial report of internal auditor  ( inspectorate )  and external auditor, Supreme Audit Agency  ( Badan Pemeriksa Keuangan) .There were two variables in this study. Audit quality was the dependent variable  ( Y ) while the independent variables elaborated into three variables, namely: auditor’s competency  ( X1 ) , auditor’s independency  ( X2 )  and auditor’s experiences  ( X3 ) . There were 36 personnel of the Inspectorate’s Office of Tomohon City participated as the sources of this study. Thus, the population of this research is the Tomohon City Regional Inspectorate officers. Data used in this study were primary and secondary data, while questioner and indepth interview as well as document study used as the data collection methods. The first consecutive methods employed to obtain primary data while the last used for obtaining secondary data. Both data analyzed using the multiple linear regression techniques.This study found that the influence of independent variable which were competency, independency and experiences towards dependent variables which was audit quality was significant. The 0.645 value of coeficient determination showed the significant relationship between both variables. This means that the equation model used in this study found the significancy at about 64,5%. The remaining proportion which was 35,5% explained by the other factors which were not part of this model. After examining the hypotheses, it can be concluded that partially competency had positive influence but not too significant to the quality of the inspectorate officer. However, independency and experiences had a positive and significant influence to the auditing quality of the public servant working in the inspectorate’s office.This study recommends to improving the knowledge and skills of the public apparatus by conducting short courses and training in accounting and auditing.Keywords: audit quality, competency, independency and experiences